Diagnóstico del gobierno abierto en la administración del GAD Parroquial Rural de Canuto, período 2021-2022 - Bazurto Muñoz, Carmen Isabel (2024)
This research project is based on an Analysis of Open Government in the local development of the rural parish of Canuto, during the period 2019-2021, its purpose is to propose an improvement plan to contribute to Open Government with the territory's resources for development. local parish as an alternative that involves citizens in the responsible decision-making process based on principles of participation, it also aims to analyze the influence of open government on local development. To focus on the problem and weaknesses, evaluation instruments were developed, such as the interview conducted with the president of the parish council and the survey directed at a sample of the population, which provided relevant information. Inductive methods were used to develop this work. , deductive and synthetic analytical. The results reflected the dissatisfaction of the inhabitants due to the unfulfilled promises, the critical knots found allowed us to recommend an improvement plan to contribute to the local development of the parish. Due to these shortcomings, it is recommended to develop an improvement plan to contribute and streamline the processes, and in the services, coverage and opportunities to participate in the Open Government for local development.